Strategic Communication and Genealogical Legitimacy: Rabithah Alawiyah’s Public Relations Response to Lineage Denial and False Habib Phenomena - Purwaningwulan, Melly Maulin; Zulkarnaen, Sayid Riziq (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2025)
The phenomenon of lineage denial and the emergence of individuals falsely claiming the status of Habib has increasingly posed a substantive challenge for Rabithah Alawiyah as a genealogical and religious authority. This study seeks to examine the public relations strategies employed by Rabithah Alawiyah in responding to these issues, particularly in navigating the contestation of genealogical authenticity and the social implications arising from the presence of illegitimate claims. Methodologically, this research adopts a qualitative approach with a case study design, enabling an in-depth exploration of Rabithah Alawiyah's communicative practices and institutional responses to the aforementioned challenges. The research utilizes the Four-Step Public Relations Process theory. Data collection techniques include in-depth interviews, non-participant observation, and document analysis. Informants were selected using purposive sampling techniques. The research findings indicate that the Rabithah Alawiyah public relations actively monitors issues through social media and community reports to identify patterns of lineage denial and false claims of Habib. The organization designs strategies based on lineage education, strengthening genealogical literacy, and building synergy with academics and religious figures. Rabithah Alawiyah optimizes digital media, seminars, and community collaborations to strengthen factual narratives. The evaluation is conducted periodically by reviewing public responses, educational programs' effectiveness, and community engagement levels to clarify the information the organization provides. The research concludes that education-based public relations strategies, information transparency, and data-driven approaches are key to maintaining the organization's credibility.